Adalimumab-induced optic neuropathy in a patient with Behçet’s syndrome - Sofia Miranda; Daniel Calado; Joana Rua; Fernando Salvador (European Journal of Case Reports in Internal Medicine)
A 37-year-old woman with a diagnosis of Behçet’s syndrome, treated with colchicine and prednisolone, maintained low disease activity for a period of 10 years, after which, she developed a new episode of anterior uveitis. A cycle of high dose systemic corticosteroids was required but the patient presented with a new flare during dose tapering. A decision to initiate a corticosteroid-sparing agent was then made, with an initially satisfactory response. However, 3 months later the ocular symptoms recurred, and a new bout of oral ulceration appeared concurrently. As a result, adalimumab was then started, but the patient presented with a sudden and severe decrease of visual acuity in her right eye 4 months later. The initial bloodwork showed no elevated inflammatory markers. A lumbar puncture showed a normal cerebrospinal fluid composition. Although these findings made it less probable that the patient’s symptoms were caused by infectious or autoimmune disease, extensive investigations directed at these possible causes were performed, with negative results. Several imaging tests were also performed, which showed no alterations. However, a sensory evoked potentials test revealed a functional compromise at the pre-chiasmatic level. An iatrogenic optic neuropathy induced by adalimumab seemed the most probable cause and a decision to suspend the treatment was made. A new cycle of high dose systemic corticosteroids consisting of three pulses of methylprednisolone followed by pred-nisolone with a quick tapering over 4 weeks was also started, with gradual improvement of visual acuity.